2009
DOI: 10.1186/1471-2202-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Statistical language learning in neonates revealed by event-related brain potentials

Abstract: Background: Statistical learning is a candidate for one of the basic prerequisites underlying the expeditious acquisition of spoken language. Infants from 8 months of age exhibit this form of learning to segment fluent speech into distinct words. To test the statistical learning skills at birth, we recorded event-related brain responses of sleeping neonates while they were listening to a stream of syllables containing statistical cues to word boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
227
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(245 citation statements)
references
References 21 publications
17
227
0
1
Order By: Relevance
“…Several earlier studies have suggested that learners can extract statistical regularities embedded in speech sequences, a phenomenon called statistical learning (Saffran et al, 1996;Saffran, 2003). Even awake and sleeping neonates and infants can extract words from speech sequences using the statistical learning strategy of word segmentation after only two minutes of listening experience, implying that the general ability of statistical learning may be innate in humans (Saffran et al, 1996;Teinonen et al, 2009;Kudo et al, 2011). Statistical learning used for locating word boundaries can also be used to acquire syntax (Saffran, 2001(Saffran, , 2002Thompson and Newport, 2007).…”
Section: Statistical Learning In Language Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several earlier studies have suggested that learners can extract statistical regularities embedded in speech sequences, a phenomenon called statistical learning (Saffran et al, 1996;Saffran, 2003). Even awake and sleeping neonates and infants can extract words from speech sequences using the statistical learning strategy of word segmentation after only two minutes of listening experience, implying that the general ability of statistical learning may be innate in humans (Saffran et al, 1996;Teinonen et al, 2009;Kudo et al, 2011). Statistical learning used for locating word boundaries can also be used to acquire syntax (Saffran, 2001(Saffran, , 2002Thompson and Newport, 2007).…”
Section: Statistical Learning In Language Acquisitionmentioning
confidence: 99%
“…A young infant (birth from 37 weeks to 8 months) uses a statistical learning strategy to recognize boundaries between words in speech sequences (Saffran et al, 1996;Teinonen et al, 2009;Kudo et al, 2011). As they grow, they begin to show a narrowing in their language perception by at least by 12 months of age.…”
Section: Statistical Learning In Language Acquisitionmentioning
confidence: 99%
“…In other research domains, infants have indeed been shown to be responsive to sequential information in stimuli streams. For instance, it has been shown that neonatal infants are susceptible to sequential grammar information in speech stimuli (Gervain, Berent, & Werker, 2012;Teinonen, Fellmann, Näätänen, Alku & Huotilainen, 2009). Infants of 8 months are susceptible to similar information in artificial sound (Marcus, Fernandes & Johnson, 2007) and from 3 months of age they are susceptible to spatiotemporal sequences (Wentworth Hait & Hood, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Second, statistical learning is available across the lifespan from neonates to older adults (e.g. [8,9]), and present in many species other than humans, including primates [10,11] and rats [12]. Third, learners are sensitive to more statistical relations than the sequential conditional relations described in terms of transitional probabilities in the original Saffran et al [1] experiments.…”
Section: Introductionmentioning
confidence: 99%